Relationships between levels of serum IgE, cell-bound IgE, and IgE-receptors on peripheral blood cells in a pediatric population. - Eleonora Dehlink (PLoS ONE, 2010)
Elevated serum immunoglobulin (Ig) E is a diagnostic marker of immediate-type allergic reactions. We hypothesize that serum IgE does not necessarily reflect total body IgE because in vivo IgE can be bound to cell surface receptors such as FcepsilonRI and FcepsilonRII (CD23). The aim of this study was to analyze the relationships between levels of serum IgE, cell-bound IgE, and IgE-receptors on peripheral blood cells in a pediatric population.Whole blood samples from 48 children (26 boys, 22 girls, mean age 10,3+/-5,4 years) were analyzed by flow cytometry for FcepsilonRI, CD23, and cell-bound IgE on dendritic cells (CD11c+MHC class II+), monocytes (CD14+), basophils (CD123+MHC class II-) and neutrophils (myeloperoxidase+). Total serum IgE was measured by ELISA and converted into z-units to account for age-dependent normal ranges. Correlations were calculated using Spearman rank correlation test.Dendritic cells, monocytes, basophils, and neutrophils expressed the high affinity IgE-receptor FcepsilonRI. Dendritic cells and monocytes also expressed the low affinity receptor CD23. The majority of IgE-receptor positive cells carried IgE on their surface. Expression of both IgE receptors was tightly correlated with cell-bound IgE. In general, cell-bound IgE on FcepsilonRI+ cells correlated well with serum IgE. However, some patients carried high amounts of cell-bound IgE despite low total serum IgE levels.In pediatric patients, levels of age-adjusted serum IgE, cell-bound IgE, and FcepsilonRI correlate. Even in the absence of elevated levels of serum IgE, cell-bound IgE can be detected on peripheral blood cells in a subgroup of patients.